Dual modality tomography for multiphase flow imaging using electrical capacitance and ultrasonic sensors - Jaysuman Pusppanathan, 1981-, author 232675; Ruzairi Abdul Rahman; Fakulti Kejuruteraan Elektrik 540663 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2016